2021
DOI: 10.1002/edm2.227
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for hypoglycaemia in people with diabetes in Denmark, 1997–2017: Time trends in incidence and HbA1c and glucose‐lowering drug use before and after hypoglycaemia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Overall, this review shows that hypoglycaemia-related hospitalisations or ED visits have declined since 2015. Although the trends in hospitalisations or ED visits seem to portray a similar pattern, there was considerable diversity in incidence rates between countries, with the lowest incidence rate (22 events per 100,000 people in 2017) being reported in Denmark [45]. Various studies that also observed the trend in antidiabetic drug use during the time found a decrease in the use of medications that have a high contribution to hypoglycaemia incidents [34,46,48].…”
Section: Interpretation Of Findings In Relation To Other Studiesmentioning
confidence: 94%
See 4 more Smart Citations
“…Overall, this review shows that hypoglycaemia-related hospitalisations or ED visits have declined since 2015. Although the trends in hospitalisations or ED visits seem to portray a similar pattern, there was considerable diversity in incidence rates between countries, with the lowest incidence rate (22 events per 100,000 people in 2017) being reported in Denmark [45]. Various studies that also observed the trend in antidiabetic drug use during the time found a decrease in the use of medications that have a high contribution to hypoglycaemia incidents [34,46,48].…”
Section: Interpretation Of Findings In Relation To Other Studiesmentioning
confidence: 94%
“…Ultimately, 35 studies met the pre-defined inclusion criteria , of which 8 studies were identified through citation analysis. Studies were published between 2005 and 2023 and conducted mainly in the United States (US) (n = 7) [24,26,36,42,47,49,52], Italy (n = 6) [23,29,31,33,41,53], Korea (n = 4) [30,38,48,55], Denmark (n = 2) [45,46], Germany (n = 2) [25,43], Greece (n = 2) [22,28], Japan (n = 2) [37,56], Portugal (n = 2) [35,44], Taiwan (n = 2) [32,50], Malta (n = 1) [51], Pakistan (n = 1) [27], France (n = 1) [54], Spain (n = 1) [39], Thailand (n = 1) [40], and the United Kingdom (UK) (n = 1) [34].…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations